Homogenous scaffold-based cranial/skull implant modelling and structural analysis-unit cell algorithm-meshless approach. - Phanindra Bogu, V; Ravi Kumar, Y; Kumar Khanra, Asit (Medical & Biological Engineering & Computing, 2017)
This computational study explores a unique modelling approach of the cranial implant, homogenous scaffold algorithm and meshless method, respectively. This meshless method is employed to review the implant underneath intracranial pressure (ICP) conditions with a standard ICP range of 7 mm of Hg to 15 mm of Hg. The algorithm is used to introduce uniform porosity within the implant enabling the implant behaviour with respect to ICP conditions. However, increase in the porosity leads to variation in deformation and equivalent stress, respectively. The meshless approach provides a valuable insight in order to know the effect of total deformation and equivalent stress (von Mises stress) and replaces the standard meshing strategies. The patient CT data (computed tomography) is processed in MIMICS software to get the mesh model. An entirely unique modelling approach is developed to model the cranial implant with the assistance of the Rhinoceros software. This modelling methodology is the easiest one and addressing both the symmetrical and asymmetrical defects. The implant is embedded in a unit cell-based porous structure with the help of an algorithm, and this algorithm is simple to manage the consistency in porosity and pore size of the scaffold. Totally six types of implants are modelled with variation in porosity and replicate the original cranial bone. Among six implants, Type 2 (porosity 82.62%) and Type 5 (porosity 45.73%) implants are analysed with the meshless approach under ICP. The total deformation and equivalent stress (von Mises stress) of porous implants are compared with the solid implant under same ICP conditions. Consequently, distinctive materials are used for structural analysis such as titanium alloy (Ti6Al4V) and polyether-ether-ketone (PEEK), respectively. The deformation and equivalent stress (von Mises stress) results are obtained through the structural analysis. It was observed from the results that the titanium-based solid implant is the best implant in all aspects, while considering weight and osseointegration PEEK-based Type 5 implant is the best one. A novel free-form closed curve network (FCN) technique is successfully developed to model a cranial implant for symmetrical and asymmetrical defects. The porous implant is adequately modelled through the unit cell algorithm and analysed through meshless approach. The implementation of 3D printed component will allow physicians to gain knowledge and successfully plan the preoperative surgery.